Impacto psicológico del Covid-19 en la salud mental, en adolescentes entre 14-15 años de una institución educativa de Riohacha (2021)
Mental health is becoming more and more important, since, like physical health, if it is affected, it has consequences in different areas of life such as personal, family and social. In addition, it interferes in the school environment, being necessary taking into account the pandemic caused by COVID-19. That is why the main objective of the present study was to analyze the psychological impact of Covid-19 on mental health in adolescents between 14-15 years old, the Denzil School Educational Institution of the Special, Tourist and Cultural District of Riohacha.